Chronicle of Malaysia : fifty years of headline news (1963 - 2013) - Mathews, Philip. (Editions Didier Millet, 2013)
"This revised and updated edition of the Chronicle of Malaysia brings the full dramatic sweep of Malaysia's history up to date, taking the reader through the nation's first 50 years from the formation of Malaysia in 1963 all the way to 2013. It is packed with illustrated news stories covering hundreds of the nation's key social, political, cultural and sporting events. As a compendium of all aspects of Malaysian life, the book captures the mood of the day with a sense of vividness and immediacy. Concise, accessible articles—revised and rewritten to engage today's readers—are introduced by headlines and liberally illustrated with photographs and specially commissioned cartoons."--Publisher's website.